NS1‐binding protein radiosensitizes esophageal squamous cell carcinoma by transcriptionally suppressing c‐Myc. Issue 1 (5th June 2018) - Wang, Yuwen; Cheng, Jingjing; Xie, Dan; Ding, Xiaofeng; Hou, Hailing; Chen, Xi; Er, Puchun; Zhang, Furong; Zhao, Lujun; Yuan, Zhiyong; Pang, Qingsong; Wang, Ping; et al.
Abstract: Background: Cisplatin‐based chemotherapy with concurrent radiotherapy is a standard treatment for advanced esophageal squamous cell carcinoma (ESCC). NS1‐binding protein (NS1‐BP), a member of the BTB‐kelch protein family, has been shown to inhibit the proliferation of Hela cells by suppressing c‐Myc. In the present study, we examined the potential function role of NS1‐BP expression in ESCC, and particularly, the sensitivity of ESCC to radiotherapy. Methods: NS1‐BP expression was examined using immunohistochemistry in two cohorts (n = 98 for the training cohort; n = 46 for independent validation cohort) of ESCC patients receiving cisplatin‐based chemotherapy and concurrent radiotherapy. Normal esophageal mucosal tissue blocks were used as a control. We also conducted a series of in vitro and in vivo experiments to examine the potential effects of over‐expressing NS1‐BP on ESCC cells, and particularly their sensitivity to ionizing irradiation. Results: In the training cohort, NS1‐BP downregulation was observed in 59% (85/144) of the ESCC specimens. NS1‐BP downregulation was associated with chemoradiotherapeutic resistance and shorter disease‐specific survival (DSS) in both the training and validation cohorts. Over‐expressing NS1‐BP in cultured ESCC cells substantially increased the cellular response to irradiation both in vitro and in vivo. NS1‐BP also significantly enhanced IR‐induced apoptosis, and abrogated IR‐induced G2 /M cell‐cycle arrest and ATM/Chk1 phosphorylation. Immunoprecipitation assays indicated that NS1‐BP could interact with c ‐ Myc promoter regions to inhibit its transcription. In ESCC tissues, c‐Myc expression was inversely correlated with NS1‐BP levels, and was associated with a shorter DSS. Conclusions: Our findings highlight the role and importance of NS1‐BP in radiosensitivity of ESCC. Targeting the NS1‐BP/c‐Myc pathway may provide a novel therapeutic strategy for ESCC.